Identification of Aesthetic Values for Visualization Media of Flood Disaster Modeling - Muhammad Yudhi Rezaldi; Rabiah Abdul Kadir; Mohamad Taha Ijab; Azlina Ahmad; Didit Widiatmoko Soewardikoen; Apip Apip (ITB Journal Publisher, LPPM ITB, 2020)
Many flood modelings use geovisualization techniques but are very complicated and can only be understood by researchers or practitioners. There is a need for modelings that are informative and can be understood by ordinary people for the purpose of disaster mitigation. This research analyzed a flood modeling geovisualization sample to find out the extent to which aesthetic values are used in that modeling. For breaking down the modeling, an analytical approach was used as well as physioplastic, ideoplastic, and judgment analyses. Then, the modeling was evaluated through a questionnaire that was distributed using Google Forms to 40 respondents with a background as visual communication design students. The questionnaire was presented using closed questions and a visual analogue scale. The aesthetic parameters used for measuring were: lighting, color, two-dimensional field, three-dimensional field, time/motion, and sound. The evaluation results showed that the flood modeling geovisualization sample did not use aesthetics effectively. Modeling representations need to be simplified into visualizations using a well-planned aesthetic concept to make them more informative. Hopefully, the result of this research will make flood modeling more impactful and easier to understand by ordinary people through the application of aesthetic values such as those addressed in the questionnaire.